Penyuluhan mengenai Gangguan Kognitif Pasca Stroke di Poliklinik Neurologi Rumah Sakit Universitas Mataram - Herpan Syafii Harahap; Ilsa Hunaifi; Muhammad Ghalvan Sahidu; Yanna Indrayana; Fitriannisa Faradina Zubaidi; Silmi Chairan Andi; Putri Nurhayati; Anjely Doni Lasmi; Ni Komang Miraditi; Yudika Ilhami Rusdi; Muhammad Ibnu Annafi; Lillah Faizah (Universitas Mataram, 2023)
Cognitive impairment is one of the important complications of stroke with a high prevalence. If not detected and managed properly, this cognitive disorder can worsen into post-stroke severe cognitive impairment (vascular dementia) with social and economic impacts on the family. This community service activity aims to increase public understanding of the importance of recognizing memory loss in stroke patients. This activity is carried out in the form of counseling at the Neurology Polyclinic at UNRAM Hospital once a week for a period of 3 weeks involving visitors to the Neurology Polyclinic at UNRAM Hospital, both outpatients and their caregivers. The participants were asked to take part in a whole series of activities which included pre-test, counseling, discussion, and post-test. The number of participants who took part in this counseling activity were 36 subjects. The participants' relatively high interest in participating in this activity can be seen from the documentation of the entire series of activities and the significant increase in the post-test mean score compared to the pre-test average score at the statistical analysis stage (p <0.05). This activity showed high effectiveness in increasing participants' understanding of memory loss in stroke patients.